ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2021 - Silviana, Heni; Mahirun, Mahirun (Oikonomia: Jurnal Manajemen, 2024)
This study aims to test and analyze the factors that influence dividend policy involving the variables of liquidity, leverage, profitability, activity ratio, and firm size in companies indexed LQ45 on the Indonesia Stock Exchange for the period 2017-2021. The analytical tool we use is multiple linear regression on SPPS software to test the effect of independent variables on the dependent variable. The findings in this study are that the activity ratio proxied by total asset turnover and firm size has a positive and significant effect. while leverage with the debt to equity ratio indicator and profitability with the return on assets indicator have a negative and significant effect. Meanwhile, another finding of our research is that liquidity with the current ratio indicator also has a positive although insignificant effect on dividend policy.